A New Method Of Human Brain Segmentation Utilizing A Class Of Power Series Solutions Of Fractional Differential. (August 2019) - Hadid, Samir B.; Ibrahim, Rabha W.; Kamaruddin, Norshaliza
Abstract: A biological dynamic system is very useful in engineering possessions such as control systems, signal processing, and bio-molecular communication networks. On the other hand, fractional differential equations are one of the main subjects that are used to solve problems in biological dynamic systems. In the current paper, we investigate a new class of fractional dynamical systems of brain segmentation. The application shows the improvement of segmentation of a class of brain images.